A new species of Trachystolodes Breuning, 1943 from Central China (Coleoptera, Cerambycidae, Lamiinae) - Wang, Yu; Xie, Guanglin; Wang, Wenkai (Zootaxa, 2021)
A new species, Trachystolodes tianjialini sp. nov., from Houhe National Nature Reserve, Hubei, China, is described and illustrated.